2006
DOI: 10.1021/jp060129g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on the Deactivation Processes of Benzophenone Ketyl Radicals in the Excited State

Abstract: The solvent effects on ketyl radicals of benzophenone derivatives (BPD) in the excited state (BPDH*(D1)) were investigated. Absorption and fluorescence spectra of BPDH*(D1) in various solvents were measured using nanosecond-picosecond two-color two-laser flash photolysis. The fluorescence peaks from BPDH*(D1) showed a shift due to the dipole-dipole interaction with the solvent molecules. The dipole moments (mu(e)) of BPDH*(D1) were estimated to be 7-10 D, indicating that BPDH*(D1) are highly polarized. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 54 publications
1
38
1
2
Order By: Relevance
“…In contrast, the photo-excitation of BPH in polar solvents is known to lead to the formation of solvated electrons. [43][44] In the present study we found no experimental evidence for the formation of solvated electrons in Bmim-TFSA. Even if an electron had been ejected from BPH, the electron would have immediately been scavenged by the Bmim cation, as we previously reported.…”
Section: Resultscontrasting
confidence: 88%
“…In contrast, the photo-excitation of BPH in polar solvents is known to lead to the formation of solvated electrons. [43][44] In the present study we found no experimental evidence for the formation of solvated electrons in Bmim-TFSA. Even if an electron had been ejected from BPH, the electron would have immediately been scavenged by the Bmim cation, as we previously reported.…”
Section: Resultscontrasting
confidence: 88%
“…The diphenylmethanol cation quickly deprotonates to regenerate MeOBP (state f). 99,120,122,132134 In the presence of an appropriate electron acceptor, the formed MePI…”
Section: New Photosensitization Using Two Laser Beams With Different mentioning
confidence: 99%
“…The reaction details and properties of the excited states of BP and its derivatives have been revealed extensively through the broad application of various time‐resolved spectroscopies, especially transient absorption (TA). For example, the properties and reaction mechanisms of the ketyl radical and the radical from the solvent and their reaction to produce a light absorbing transient (LAT) have been reported . The intersystem crossing from S 1 to T 1 for BP and its derivatives has been observed directly by ultrafast TA with measured rates of ~10 11 s –1 , and a rapid water addition process to the protonated BP triplet was identified to result in the fast deactivation of the triplet BP in acidic aqueous solution .…”
Section: Introductionmentioning
confidence: 99%
“…The photoreduction of aromatic ketones especially benzophenone (BP) and its derivatives has received much attention over the years and a number of studies have been reported. [1][2][3][4][5][6][7][8][9][10]13,27,31,33] It is well-known that the hydrogen abstraction reaction of BP and its derivatives typically arises from their np* excited triplet state that can react with a hydrogen donor molecule to produce a corresponding ketyl radical and free radical of the hydrogen donor molecule. This kind of reaction may proceed by either a direct hydrogen atom transfer or a coupled electron/proton transfer.…”
Section: Introductionmentioning
confidence: 99%